Depth resolved snapshot energy-dispersive X-ray diffraction using a conical shell beam - Dicken, A. J.; Evans, J. Paul O.; Rogers, Keith; Prokopiou, Danae; Godber, S. X.; Wilson, M. (Optical Society of America, 2017)
We demonstrate a novel imaging architecture to collect range encoded diffraction patterns from overlapping samples in a single conical shell projection. The patterns were measured in the dark area encompassed by the beam via a centrally positioned aperture optically coupled to a pixelated energy-resolving detector. We show that a single exposure measurement of 0.3 mAs enables d-spacing values to be calculated. The axial positions of the samples were not required and the resultant measurements were robust in the presence of crystallographic textures. Our results demonstrate rapid volumetric materials characterization and the potential for a direct imaging method, which is of great relevance to applications in medicine, non-destructive testing and security screening.
© 2017 Optical Society of America